An Unusual Complication of Crawford Tube Insertion. Issue 1 (January 2015) - Fan Gaskin, Jennifer C.; Gaskin, Brent J.
<x xml:space="preserve">Abstract</x> The authors describe an unusual and challenging complication of bicanalicular (Crawford) stent insertion that has previously never been reported. A 27-year-old man sustained multiple lacerations to the left (L) periocular and facial areas with a glass bottle. He was admitted under the care of the Plastic Surgical team at another institution and underwent repair of the facial, eyelid, and canalicular lacerations in the operating room. During the surgery, a Crawford stylet was guided in the L inferior canaliculus but was not retrieved nasally. Neuroimaging revealed that the metallic stylet of the Crawford tube was within the orbit, extending via the superior orbital fissure into the middle cranial fossa. The patient was then transferred under the care of the neurosurgical team and underwent a combined orbital/neurosurgical procedure to retrieve the stylet.